2013
DOI: 10.1016/s2214-109x(13)70067-6
|View full text |Cite
|
Sign up to set email alerts
|

Abbreviated HIV counselling and testing and enhanced referral to care in Uganda: a factorial randomised controlled trial

Abstract: SummaryBackgroundHIV counselling and testing and linkage to care are crucial for successful HIV prevention and treatment. Abbreviated counselling could save time; however, its effect on HIV risk is uncertain and methods to improve linkage to care have not been studied.MethodsWe did this factorial randomised controlled study at Mulago Hospital, Uganda. Participants were randomly assigned to abbreviated or traditional HIV counselling and testing; HIV-infected patients were randomly assigned to enhanced linkage t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 27 publications
1
32
0
Order By: Relevance
“…Five tested the effect of POC testing using Alere Pima machines [8,19,20,22,29] and two used same day BD FACS Count results [11,21]. One study did not report the sample size or a CI for its reported RR so could not be included in the meta-analysis [22].…”
Section: Resultsmentioning
confidence: 99%
“…Five tested the effect of POC testing using Alere Pima machines [8,19,20,22,29] and two used same day BD FACS Count results [11,21]. One study did not report the sample size or a CI for its reported RR so could not be included in the meta-analysis [22].…”
Section: Resultsmentioning
confidence: 99%
“…Disclosure of HIV status and partner referral are important in establishing social support and helping prevent transmission of the virus to sexual partners as well as enabling both patients and partners to access appropriate HIV services (Chersich and Temmer-man 2008). The main aim of HCT services is to ensure clients testing HIV positive are linked care and treatment services, however a study conducted in Uganda by Wanyenze et al (2013) has suggested an enhanced linkage approach that has significantly reduced ART initiation time. As opposed to merely providing information about nearby support services this approach includes counselling about barriers to care, assisted disclosure and a scheduled appointment at an ART clinic as well as reminders by phone or home visits.…”
Section: Discussionmentioning
confidence: 99%
“…There is also evidence that counsellors modify rules in the course of doing their jobs due to several factors including an attempt to tailor the counselling to individual needs (Angotti 2010), however in so doing they may exclude key messages and consequently compromise the quality of service rendered to clients. Wanyenze et al (2013) have suggested that HIV testing can be integrated into routine health care without a lengthy counselling session particularly in settings where there are shortages of health workers however it is crucial that clients that test HIV positive are provided with more intensive post-test counselling and follow-up to ensure enrolment into care and timely treatment initiation.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing the coverage of HTS through community outreach testing when provided within WHO's essential 5Cs: Consent, Confidentiality, Counselling, Correct test results and Connection has the benefit of early Positive client linkage to care [1]. This further improves the overall treatment outcome and reduces the risk of possible transmission of infection, while negative clients are offered other prevention models to adopt, aiding them to remain negative with an added advantage of increased HIV risk perception index which is associated with improved motivation for risk reduction [2,3].…”
Section: Introductionmentioning
confidence: 99%